2021
DOI: 10.1111/cea.13959
|View full text |Cite
|
Sign up to set email alerts
|

Comparative features of eosinophilic and non‐eosinophilic asthma

Abstract: To the Editor, Studies looking specifically at the prevalence of eosinophilic phenotypes in mild asthma are required. In patients with corticosteroidnaïve asthma, we reported that high eosinophil counts do not necessarily translate into clinical symptoms or lower lung function. 1 However, in asthma of all severities, eosinophils are linked to the worst outcomes. 2 As such, early identification of mild/very mild asthma patients with significant eosinophilia could be a marker of increased risk of such events to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…3 While eosinophils are usually thought to be potent inflammatory cells and active contributors to asthma severity, some authors have suggested that lung tissue may actually harbour a population of regulatory eosinophils, the function of which might be to dampen airway inflammation. 4 A recent study has highlighted the existence of a group of patients with mild asthma and high sputum eosinophil count 5 questioning the detrimental action of eosinophils in shaping disease severity and perhaps suggesting heterogeneity in their functional roles.…”
Section: R E S E a R C H L E T T E R A Clustering Analysis Of Eosinop...mentioning
confidence: 99%
“…3 While eosinophils are usually thought to be potent inflammatory cells and active contributors to asthma severity, some authors have suggested that lung tissue may actually harbour a population of regulatory eosinophils, the function of which might be to dampen airway inflammation. 4 A recent study has highlighted the existence of a group of patients with mild asthma and high sputum eosinophil count 5 questioning the detrimental action of eosinophils in shaping disease severity and perhaps suggesting heterogeneity in their functional roles.…”
Section: R E S E a R C H L E T T E R A Clustering Analysis Of Eosinop...mentioning
confidence: 99%
“…Patients with EA exhibit worse symptoms than those with non-EA (non-eosinophilic asthma (NEA)), regardless of asthma severity. 1 Recent studies have confirmed the crucial involvement of innate lymphoid cells (ILC2s), a rare group of lymphocytes, in innate immune responses to allergic diseases. 2 Innate lymphoid cells lack antigen recognition receptors and produce IL-13 and IL-5, both of which are involved in EA pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Asthma, a prevalent chronic airway illness, is classified into the eosinophilic asthma (EA), neutrophilic asthma, mixed asthma, and paucigranulocytic asthma based on the counts of eosinophils and neutrophils in the sputum. Patients with EA exhibit worse symptoms than those with non‐EA (non‐eosinophilic asthma (NEA)), regardless of asthma severity 1 . Recent studies have confirmed the crucial involvement of innate lymphoid cells (ILC2s), a rare group of lymphocytes, in innate immune responses to allergic diseases 2 …”
Section: Introductionmentioning
confidence: 99%